All-trans retinoic acid improves NSD2-mediated RARα phase separation and efficacy of anti-CD38 CAR T-cell therapy in multiple myeloma. Issue 3 (14th March 2023) - Peng, Ziyi; Wang, Jingya; Guo, Jing; Li, Xin; Wang, Sheng; Xie, Ying; Jiang, Hongmei; Wang, Yixuan; Wang, Mengqi; Hu, Meilin; Li, Qian; Wang, Yafei; et al.
Abstract : Background: Immunotherapies targeting CD38 have demonstrated salient efficacy in relapsed/refractory multiple myeloma (MM). However, loss of CD38 antigen and outgrowth of CD38 negative plasma cells have emerged as a major obstacle in clinics. All-trans retinoic acid (ATRA) has been reported to upregulate CD38 expression, but the mechanism and adaptive genetic background remain unexplored. Methods: The efficacy of ATRA in upregulating CD38 expression in MM cells is evaluated by flow cytometry. The interaction between NSD2 and the RARα is analyzed by immunoprecipitation, and the nuclear condensation of RARα is evaluated under laser confocal microscope. A graft model of MM is established in NOD. Cg-Prkdc scid Il2rg tm1Wjl /SzJ mice, and the tumor burden is assessed by in vivo fluorescence imaging. Results: We report that ATRA upregulates MM cells CD38 in a non-linear manner, which is t(4;14) translocation dependent, and t(4;14) translocation-induced NSD2 shows positive correlation with ATRA-induced level of, but not with basal level of CD38 expression. Mechanistically, NSD2 interacts with the ATRA receptor, RARα, and protects it from degradation. Meanwhile, NSD2 enhances the nuclear condensation of RARα and modifies the histone H3 dimethylation at lysine 36 on CD38 promoter. Knockdown of NSD2 attenuates the sensitization of MM against ATRA induced CD38 upregulation. Translationally, ATRA is prone to augment the efficacy of anti-CD38 CAR T cells in NSD2 high MM cells in vitro and in vivo. Conclusion: This study elucidates a mechanism of ATRA in regulating CD38 expression and expands the clinical potential of ATRA in improving immunotherapies against CD38 in patients with MM.Cite Now